(untitled) (Arquivo Maaravi: Revista Digital de Estudos Judaicos da UFMG, 2014)
The present article analyzes the confessional rhetoric characteristic of the novel Por que sou gorda, mamãe?, by Cíntia Moscovich. First, this study aims to identify the narrative strategies used by the gaúchan author to leave marks of the rhetoric of confession in all the interstices of the text, in a cyclical dynamics. To this end, it draws on the reflections of Philippe Lejeune about writing in first person as well as on those of Jacques Derrida about the autoimmune nature of the autobiographical text. Second, this article focuses on the origins and the different facets of guilt that the narrator suffers from, leaning on her relationship with the female body and the notion of guilt in Judaism. Moacyr Scliar’s essay Enigmas of guilt contributes with essential elements to understand the specificity of the feeling of guilt in the Jewish tradition.